2014
DOI: 10.3141/2406-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Realistic Heat-Straightening Repair on Damaged Steel Beams

Abstract: Realistic implementation of heat straightening in the field can include imperfections such as temperatures much higher or lower than recommended values, overstraining, mechanical hot bending, and multiple heat straightening. Experimental investigations were performed to evaluate the effects of realistic heat straightening with imperfections on damaged steel beams. Six steel beam specimens were fabricated from A36 steel plates and tested to evaluate the effects of various damage and repair parameters on realist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Experimental investigations were conducted to evaluate the effects of damage followed by realistic heat straightening repair (with imperfections) on the material properties and serviceability of large-scale steel beam bridges. The test bridge was constructed following an analysis of an Indiana Department of Transport database developed during previous research ( 1 , 2 ). The analysis indicated that: (i) A36 was the most frequently damaged-repaired steel type, (ii) composite continuous bridges were the most frequently damaged-repaired structure type, and (iii) considering elastic rebound of the damaged steel, 30 times the yield strain (ε y ) was typically the maximum average damage amount.…”
Section: Experimental Investigationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental investigations were conducted to evaluate the effects of damage followed by realistic heat straightening repair (with imperfections) on the material properties and serviceability of large-scale steel beam bridges. The test bridge was constructed following an analysis of an Indiana Department of Transport database developed during previous research ( 1 , 2 ). The analysis indicated that: (i) A36 was the most frequently damaged-repaired steel type, (ii) composite continuous bridges were the most frequently damaged-repaired structure type, and (iii) considering elastic rebound of the damaged steel, 30 times the yield strain (ε y ) was typically the maximum average damage amount.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…In previous research ( 2 ), the most detrimental deviations commonly found in field applications of heat straightening were: (a) underheating below 1200°F (about 800°F), (b) overheating above 1200°F (about 1400°F), (c) overstraining above the recommended restraining force limit, and (d) multiple heat straightening of the same beam more than two times.…”
mentioning
confidence: 90%
See 3 more Smart Citations